The Forging a Harmonious Relationship between Cyberspace and the Real World - Suryani, Wahidah; Mashadi, Mashadi (Proceeding International Conference on Religion, Science and Education, 2024)
The virtual world is growing with the birth of some astonishing innovations. This development has created a significant distance between the virtual and real worlds. In cyberspace, communication can be done with people from all over the world quickly, while in the real world, it takes time due to distance limitations. However, many positive things can be taken from the development of cyberspace technology. First, the development of many fields of study in the real world, for example, education, with the ease of learning online. Second, cyberspace technology facilitates human activities in the real world. This article is written to explain various further efforts to overcome the gap between the two worlds and create harmony. The discussion in this article is based on the literature review method and refers to new media theory. The discourse of this article centers on several efforts: the importance of creating harmony between the virtual and real worlds, the presence of technology that can bridge the virtual and real worlds, and the collaboration of the government and users to realize this harmony.